2011
DOI: 10.1590/s0101-31222011000200016
|View full text |Cite
|
Sign up to set email alerts
|

Pré-hidratação e avaliação do potencial fisiológico de sementes de soja

Abstract: Sementes de soja submetidas à rápida hidratação podem sofrer danos por embebição, cuja intensidade depende do cultivar e do teor de água inicial das sementes. O presente trabalho objetivou estudar alterações fisiológicas determinadas por métodos de pré-hidratação para minimização do dano por embebição. Foram utilizados três lotes de cada cultivar de soja, de tamanho uniforme, CD 202 e CD 215, caracterizados quanto ao teor de água, germinação, primeira contagem de germinação, envelhecimento acelerado, condutivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 17 publications
0
10
0
6
Order By: Relevance
“…The prejudicial effects of seed quick soaking may be the main cause of the decrease in the germination capacity of seeds, since it is the reorganization speed of the membrane system that reflects the vigor of seeds (Tilden and West, 1985). In works developed by Costa et al (2002) and Silva and Villela (2011), authors observed that soybean seeds with lower physiological quality presented higher water absorption rates during the first hours of the soaking process. Rossetto et al (1997) observed that the decrease in the soaking speed of soybean seeds reduced damages caused by soaking.…”
Section: Resultsmentioning
confidence: 99%
“…The prejudicial effects of seed quick soaking may be the main cause of the decrease in the germination capacity of seeds, since it is the reorganization speed of the membrane system that reflects the vigor of seeds (Tilden and West, 1985). In works developed by Costa et al (2002) and Silva and Villela (2011), authors observed that soybean seeds with lower physiological quality presented higher water absorption rates during the first hours of the soaking process. Rossetto et al (1997) observed that the decrease in the soaking speed of soybean seeds reduced damages caused by soaking.…”
Section: Resultsmentioning
confidence: 99%
“…If lack of water retards germination of the seeds and development of the seedlings, what may even lead them to death (Silva et al, 2006), and depending on intensity and/or extent of such water restriction (Moraes and Menezes, 2003), the fast imbibition caused by excess moisture available in environment, may result in damage to membranes of the seeds, thereby increasing rate of damages caused by overimbibition (Silva and Villela, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Contudo, ainda é subutilizada pelo sistema de produção, não havendo informações estatísticas (SILVA et al, 2008) nem padrões estabelecidos para a produção e comercialização de sementes dessa espécie (REIS et al, 2010).…”
Section: Introductionunclassified